Estrategias metodológicas para fortalecer los valores en las y los estudiantes del cuarto año de educación general básica, de la escuela Teniente Hugo Ortiz N° 2 de la cuidad de Loja. Período académico 2014 - 2015. - Quirola Achupallas, Jackeline Maribel (2016)
The development of the thesis METHODOLOGICAL STRATEGIES TO STRENGTHEN VALUES IN THE STUDENTS OF THE FOURTH YEAR OF BASIC EDUCATION SCHOOL TENIENTE HUGO ORTIZ N°2 OF THE CITY OF LOJA. ACADEMIC YEAR 2014 - 2015, had as its overall objective to apply methodological strategies to strengthen the values in the fourth grade students of Basic Education; the methodology used is explanatory nature, quasi-experimental, transversal field, because had to go to the place where the events took place to explain the relationship between the application of methodological strategies and the strengthening of values, at a time and given space. Inductive method, deductive method, and as a technique: the survey with its instrument, the questionnaire, which was sent to the teacher and 21 students, in their order using theoretical methods as was also necessary. The application of the alternatives, where he had planned to develop activities and processes, allowed to reach the systematization and analysis of the results, where students show attitudes and behaviors that demonstrate the practice of values after using methodological strategies the teaching-learning process; and so it came to be established as the main conclusion that the application of existing methodological strategies helps teachers improve student attitudes, and thus to strengthen the values during the teaching-learning process, making upright bodies in society.